'He doesn't deserve to be in the higher track': teachers' justifications in student tracking discussions. Issue 4 (4th July 2022) - Cohen Zamir, Avner; Lefstein, Adam; Feniger, Yariv
ABSTRACT: This study examines teachers' justifications for their student sorting decisions in two Israeli secondary schools. Combining descriptive statistics and micro-ethnographic discourse analysis of 281 audio-recorded discussions, the study offers a new perspective on tracking's multiple social and organizational functions: providing students' needs, rewarding and punishing students, satisfying teachers' emotional needs, and efficiently using school resources. Most of the justifications were related to students' needs (43%) and reciprocity issues (37%), with productivity justifications (20%) appearing less frequently. The study points in particular to teacher emotions as a key factor in the tension between formal sorting requirements and teachers' sorting practices.